ARSITEKTUR KOLONIAL RUMAH SAKIT DARMO DAN FAKTOR PERUBAHAN FUNGSI RUANG - Anjasmara, Mega (Humanis; Volume 1. No. 2. Desember 2012, 2012)
This thesis discusses "Colonial Architecture Darmo Hospital and Factor Change Function Spaces". The building was built in 1921. Besides Darmo Hospital is a monumental building brainchild of legendary architect C. Citroen. Based on the purpose of the study, the type of research used in this study is using a qualitative approach. The Stages of research was conducted on the stage of data collection, processing stages, and data analysis. In the data collection techniques used are observation, study, and interviews. As for the analysis of qualitative data analysis is used to explain the causes of change in function space as well as physically. Stylistic analysis and morphological analysis is used to determine the ornaments, color, decoration, and serves to identify architectural Darmo Hospital. Architecture located in buildings Darmo Hospital is a modern architecture influenced by Art Deco style. Art Deco style is modern decorative art or decorative style that was born after World War II, Factors affecting the change in the function room and physically due to age or periodicity are factors that cause a portion of the building suffered wear or damage, design trends change factor is the changing demands of the age or style because competition among hospitals, a factor which needs include the need for space the increasing number of patients and the number of facilities that require new space, and activity factor which is the number of activities going on at the hospital that cause stains or dirt specific section on hospital premises.
Keywords: Architecture, Function Room, Darmo Hospital